An outdoor-indoor coupled simulation framework for Climate Change–conscious Urban Neighborhood Design. (August 2014) - Peng, Chengzhi; Elwan, Amr
Only recently, research communities and professional organizations have started to incorporate the factor of climate change in software-based environmental simulation with a view to inform climate adaptation planning and design. Based on the results from simulating a neighborhood design proposed for New Cairo, Egypt, we develop a conceptual framework and an environmental simulation workflow aimed at achieving Climate Change–conscious Urban Neighborhood Design (C3UND). Central to the C3UND approach is the coupling of neighborhood outdoor simulation and building indoor simulation and taking into account climate change scenarios as projected by today's meteorological modeling. Utilizing two existing software systems, ENVI-met for urban neighborhood outdoor simulation and Ecotect for building indoor simulation, we demonstrate how a workflow can be implemented to play out climate change scenarios on urban neighborhoods and the buildings located within. The C3UND simulation framework and workflow was further applied to a neighborhood site at the Sheffield University campus in England with weather data input of the present day (2012) and of the 2050s generated by the CCWorldWeatherGen tool. Our current study suggests that environmental simulation of climate change scenarios at an urban neighborhood scale is currently achievable but not without considerable gaps. Use of additional three-dimensional virtual neighborhood models, for instance, is required to bring outdoor and indoor simulation outcomes together through graphic overlay to enable more intuitive and holistic understanding of potential climate change impacts. The implications of the C3UND framework for sustainable urban and architecture design are discussed, leading to a list of research questions to be further investigated.